Influence of the motor and functional abilities to the efficiancy of football techniques elements performance - Talovic, M.; Hodzic, M.; Bajramovic, I.; Jeleskovic, E.; Alic, H. (Homosporticus, 2009)
Goal of this research is to confirm influence of the predictor`s summary, motor and functional variables to the criteria variables of performance football techniques elements among 88 football players` ages 12-14 years. Eighteen variables were used for the motor abilities estimation, two variables for the functional abilities estimation and fifteen variables for the football techniques elements performance. Manifolds regression analysis is used for the confirmation of predictor`s influence to the criteria, with witch we tried to define witch variables of predictor`s system (motor and functional abilities) mostly define criteria variable that represents general success while realization of move-technical elements of football. Our interest was how predicting system of motor and functional abilities influence learning efficiency and football techniques elements performance. Regression analysis was done and it points the connection of system of predictors and criteria, and criteria variable represents first main component in which all element of football techniques are saturated. Result was that that system of criteria variables are connected to the predictor`s system with high coefficient .83 and part of variability of predictive values of 69% is explained. As follows, we can surely say that this high coefficient is in function of best realization of moving structure in football. Percentage of inexplicable variability with this predictive system would probably define some other characteristics and abilities that didn`t fit into this research.